Perlindungan Hak Asasi Manusia dan Penegakan Hukum Terhadap Penyelundupan Orang Lintas Negara - Armilia, Ine; Ilmih, Andi Aina (Media Hukum Indonesia (MHI), 2024)
Human smuggling is a complex and deeply troubling issue that transcends national borders, posing significant challenges to law enforcement and human rights protection worldwide. This article explores the multifaceted aspects of human smuggling, including the factors driving it, law enforcement efforts to combat it, and the protection of human rights for its victims.The discussion begins by examining the factors that fuel human smuggling, such as economic instability, conflict, climate change, and political and social factors. These drivers lead individuals to seek better opportunities outside their home countries, often falling prey to traffickers in the process. Subsequently, the article delves into the legal frameworks at both national and international levels governing human smuggling and the role of law enforcement agencies in prevention and prosecution. Collaboration among nations is highlighted as crucial in addressing this transnational crime effectively. Furthermore, the importance of protecting the human rights of smuggling victims is emphasized. This includes providing comprehensive rehabilitation and reintegration services, ensuring access to legal protection and justice, and the active involvement of civil society organizations in supporting victims. In conclusion, the article underscores the need for coordinated efforts at the global, national, and community levels to combat human smuggling effectively. By addressing its root causes, strengthening law enforcement measures, and prioritizing victim protection, we can work towards creating a safer and more just world for all.